2012
DOI: 10.1371/journal.pone.0047805
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Antibodies against Infused Alpha-Galactosidase A in Fabry Disease on Plasma and Urinary (lyso)Gb3 Reduction and Treatment Outcome

Abstract: IntroductionEnzyme replacement therapy (ERT) with alpha-Galactosidase A (aGal A) may cause antibody (AB) formation against aGal A in males with Fabry disease (FD). Anti agalsidase ABs negatively influence globotriaosylceramide (Gb3) reduction. We investigated the impact of agalsidase AB on Gb3 and lysoGb3 and clinical outcome in Fabry patients on ERT.MethodsAdult male and female patients on ERT for at least one year were included. Urinary Gb3 was measured by HPLC, plasma lysoGb3 by LC-ESI-MS/MS and AB with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
114
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 29 publications
4
114
1
Order By: Relevance
“…Two recent studies demonstrated that antibody formation results in serum-mediated ERT inhibition, affecting the Gb3 clearance in ERT i+ men with FD. 4,7 However, the longterm effect of serum-mediated ERT inhibition on clinical outcome remains elusive. By establishing a similar approach for in vitro serum-inhibition measurement, defining ERT i+ as .50% ERT inhibition, we confirm previous data 4,7 and provide new evidence for an association between ERT inhibition and more severe end-organ manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two recent studies demonstrated that antibody formation results in serum-mediated ERT inhibition, affecting the Gb3 clearance in ERT i+ men with FD. 4,7 However, the longterm effect of serum-mediated ERT inhibition on clinical outcome remains elusive. By establishing a similar approach for in vitro serum-inhibition measurement, defining ERT i+ as .50% ERT inhibition, we confirm previous data 4,7 and provide new evidence for an association between ERT inhibition and more severe end-organ manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to male patients with FD, the mean ERT inhibition did not differ significantly between women (P=0.1385; Figure 1B). To analyze whether ERT inhibition depends on the applied product and to confirm previous studies concerning the crossreactivity of antibodies, 4,7 inhibition assays were performed in a crossover design with agalsidase-a as well as agalsidase-b for male patients under ERT. Linear regression revealed that the value of mean ERT inhibition is product-independent, indicating no measurable specific inhibition for any product (r 2 =0.93; P,0.0001).…”
Section: Ert Inhibition Status In Patients With Fdmentioning
confidence: 94%
See 3 more Smart Citations